Theoretıcal research of reınforced concrete materıals and theır applıcatıon ın the preparatıon of long-term support zones - Gasanov, Arzuman (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This article is devoted to a theoretical study of reinforced concrete materials and their use in the construction of long-term strongpoints. The relevance of this research lies in the development of modern methods for determining the strength of reinforced concrete materials as their primary indicator. This is driven by the necessity of using such materials and opens up prospects for their application in the military field. The paper presents a physical and mathematical method for determining the strength of reinforced concrete materials. approaches Theoretical methods were used. The innovation lies in the integration of physical and mathematical approaches to studying the strength of materials, which allows for the preliminary determination of the use of reinforced concrete materials for military purposes. Determining the strength of reinforced concrete materials, as a scientific result, has important practical implications for the preparation of long-term strongholds.